Voices for Change: Stakeholder Perspectives on Childhood Diagnostic Delays in Western Australia - Shane Grundy; Declan R. Walter; Lucy M. Macloughlin; Melinda Bridges; Frank D. Baughman (Child: Care, Health and Development, 2026)
ABSTRACT Background Timely access to developmental assessment services for children is essential, yet diagnostic delays persist even in nations with advanced healthcare systems. In Western Australia (WA), a recent parliamentary inquiry revealed over 17 000 children awaiting developmental assessments, with median wait times for specialist appointments reaching 15.1 months. Method Using a qualitative design underpinned by a social constructionist epistemology, this study examined the perspectives of parents ( n = 17), educators ( n = 10) and healthcare professionals ( n = 9) in WA through open‐ended survey questions analysed via mixed content analysis. We aimed to identify commonalities in stakeholder experiences with diagnostic delays and potential solutions. Results Stakeholders consistently identified insufficient funding (22 instances), extended wait times (44 instances) and lack of support (110 instances) as primary concerns. Parents reported significant stress navigating the system and frustration with ‘wait and see’ approaches; educators highlighted inadequate staffing and challenges supporting undiagnosed students; and healthcare professionals emphasised the need for more efficient referral processes and increased specialist availability. Conclusion Findings underscore the need for increased funding and workforce incentives, improved inter‐stakeholder communication and referral processes and clearer diagnostic pathway information. These cross‐sector perspectives offer actionable recommendations for policy reform aimed at reducing diagnostic delay for children in WA.